A Lightweight and Reliable Routing Approach for in-Network Aggregation in Wireless Sensor Networks - Vinitha, G; Bhuvaneshwari, K (International Journal of Computer Sciences and Engineering, 2025)
A focal issue in sensor network security is that sensors are defenseless to physical catch attacks. Once a sensor is traded off, the foe can without much of a stretch dispatch clone attacks by reproducing the bargained node, dispersing the clones all through the network, and beginning an assortment of insider attacks. Past conflicts with clone attacks experience the ill effects of either a high correspondence/stockpiling overhead or a poor discovery precision. Wireless Sensor Networks (WSNs) offer an incredible chance to screen conditions, and have a great deal of fascinating applications, some of which are very touchy in nature and require full verification secured condition. The security components utilized for wired networks can't be specifically utilized as a part of sensor networks as there is no user-controlling of every individual node, wireless condition, and all the more significantly, rare vitality assets. In this composition, we address a portion of the extraordinary security dangers and attacks in WSNs. In our proposed work, a novel clone detection framework, called CSI to overcome the previous clone detection problems. We introduce two algorithms are CSI-1 and CSI-2.The CSI-1 (Ordinary Compressed Sensing-Based Approach) algorithm used to construct an aggregation tree. The CSI- 2 (Random Projection-Based Approach) is used to reduce the communication cost. Our proposed CSI method not only achieves lowest communication cost but also manage the network trafﬁc evenly spread over sensor nodes. The presentation and security of CSI will be demonstrated feasibility of clone detection.